Adipocyte-derived kynurenine promotes obesity and insulin resistance by activating the AhR/STAT3/IL-6 signaling - Huang, Teng; Song, Jia; Gao, Jia; Cheng, Jia; Xie, Hao; Zhang, Lu; Wang, Yu-Han; Gao, Zhichao; Wang, Yi; Wang, Xiaohui; He, Jinhan; Liu, Shiwei; et al. (Nature communications, 2022)
Aberrant amino acid metabolism is a common event in obesity. Particularly, subjects with obesity are characterized by the excessive plasma kynurenine (Kyn). However, the primary source of Kyn and its impact on metabolic syndrome are yet to be fully addressed. Herein, we show that the overexpressed indoleamine 2,3-dioxygenase 1 (IDO1) in adipocytes predominantly contributes to the excessive Kyn, indicating a central role of adipocytes in Kyn metabolism. Depletion of Ido1 in adipocytes abrogates Kyn accumulation, protecting mice against obesity. Mechanistically, Kyn impairs lipid homeostasis in adipocytes via activating the aryl hydrocarbon receptor (AhR)/Signal transducer and activator of transcription 3 /interleukin-6 signaling. Genetic ablation of AhR in adipocytes abolishes the effect of Kyn. Moreover, supplementation of vitamin B6 ameliorated Kyn accumulation, protecting mice from obesity. Collectively, our data support that adipocytes are the primary source of increased circulating Kyn, while elimination of accumulated Kyn could be a viable strategy against obesity. Kynurenine, a tryptophan metabolite, is increased in the circulating plasma of obese individuals, but the source has been unclear. Here, the authors show in mice that mature adipocytes produce kynurenine, with vitamin B6 administration preventing accumulation and protecting against high-fat diet.